1997
DOI: 10.1111/j.1440-1819.1997.tb02584.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from neuroendocrinological abnormalities and frontal hypoperfusion after remission in a case with rapid cycling bipolar disorder

Abstract: A 51-year-old Japanese woman who had been suffering from a rapid cycling affective disorder (RCAD) for 24 years responded to combined clonazepam and carbamazepine therapy. Before remission, she showed neuroendocrinological and neuroimaging abnormalities such as subclinical hypothyroidism with exaggerated response to thyrotropin releasing hormone (TRH) injection, non-suppression on the dexamethasone suppression test (DST) and hypofrontality in cerebral blood flow. Her symptoms improved remarkably soon after adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Adler (1986) and Zetin and Freedman (1986) reported efficacy of clonazepam in a case of bipolar disorder in the depressive phase. Shimizu et al (1997), Sugimoto et al (2003), and Mashiko et al (2004) reported efficacy of clonazepam in a refractory case of rapid cyclic bipolar disorder. These case reports suggest that clonazepam may be useful in refractory cases of bipolar disorder depression.…”
Section: Indicationsmentioning
confidence: 95%
“…Adler (1986) and Zetin and Freedman (1986) reported efficacy of clonazepam in a case of bipolar disorder in the depressive phase. Shimizu et al (1997), Sugimoto et al (2003), and Mashiko et al (2004) reported efficacy of clonazepam in a refractory case of rapid cyclic bipolar disorder. These case reports suggest that clonazepam may be useful in refractory cases of bipolar disorder depression.…”
Section: Indicationsmentioning
confidence: 95%
“…Binding studies in rats revealed a high retention of corticosterone ( 3 H-CORT) in the cortex, particularly in the medial prefrontal regions (Diorio, Viau, & Meaney, 1993;McEwen et al, 1968). Other studies in rats (Bagley & Moghaddam, 1997;Feldman & Conforti, 1985;Moghaddam, Bolinao, Stein-Behrens, & Sapolsky, 1994) and humans (Murros, Fogelholm, Kettunen, & Vuorela, 1993;Shimizu et al, 1997) have shown that the prefrontal cortex is a significant target for the negativefeedback actions of circulating glucocorticoids (Feldman & Conforti, 1985;Moghaddam et al, 1994), which suggests that this area could play a significant role in the acute effects of corticosteroids on cognitive function.…”
mentioning
confidence: 99%
“…The discrepancy from the above prospective HPA studies may reflect differences in the clinical sample or the different time periods since the last episode. Schmizu and colleagues [11] describe a case in which the DST response normalized after 2 years of remission in a previously rapid-cycling patient, suggesting a long lag between symptomatic recovery and normalization of the HPA axis. In our study, three patients satisfied the criteria of the Newcastle euthymia protocol [12] and had therefore been in prospectively verified remission for at least the 4 weeks preceding the endocrinological investigation.…”
Section: Discussionmentioning
confidence: 99%